SOSIAL BUDAYA PERLADANGAN DAYAK KERABAT DI DESA TAPANG PERODAH KECAMATAN SEKADAU HULU KABUPATEN SEKADAU - Marthin, Martinus (JPMIS)
This research is background of the worries about tradition knowledge about fields of Dayak of Kerabat will destroyed of palm expansion in up stair of Sekadau (Sekadau Hulu) district. Researched by qualitative method of observation and interview was done for 3 months in Tapang Perodah Village. The problems would be answer in these case are; (1) The system of believe of Dayak Kerabat which based on fields effort. (2) The stages of fields of paddies stages of Dayak Kerabat done. The achievement was showing that Dayak Kerabat people believed, that in order to get fortune, healthy and saving in their life, was not only work hard but, hope that the God help them. In another words tradition religion in their life teaches them that all their activities was the God works, out of human abilities. In daily life of Dayak Kerabat is still believe that the Gods including aqriculture system. They believe that the Gods influences their activities and many other thing they do. In doing their agriculture there many special things that including Dayak Kerabat tradition. These are noticed as the condition of field of paddies ways, such as asking for permission to the leader looking for forest with follow the conditions requirements, such as the natures or the believing that the natures will give fortune or unlucky. The Kerabat people believe in this century the forest is unfertile including fields of paddies, different with the pass. This condition is because of human being activities. The peoples disobey the way to plant paddies. The stages to plant paddies for Dayak Kerabat as bellow: chopping off (nobas) cutting (nobang), fire (nucul) planting (nugal) drawing (merumput) and harvest (ngotum). After harvest followed by thankful had called gawai. This stages show us the oriented their fields of paddies make, that will not to increase up their income but to show that they care as the relationship between human being and their power God. Because this research is not too specific so we suggest to enlarge the research up next. Key word: social, cultural, paddies field, Dayak Kerabat